Hidden structural phase transition assisted ferroelectric domain orientation engineering in Hf0.5Zr0.5O2 films - Yuyan Fan; Shunda Zhang; Zhipeng Xue; Yulong Dong; Danyang Chen; Jiahui Zhang; Jingquan Liu; Mengwei Si; Chunlai Luo; Wenwu Li; Junhao Chu; Yanwei Cao; et al. (Nature Communications)
Abstract The polarization of HfO2-based ferroelectrics originates from the metastable orthorhombic phase formed during the tetragonal to monoclinic phase transition and is typically controlled by tuning the phase content. However, another way to control polarization via modulating ferroelectric domain orientations remains underexplored. This work uncovers a hidden tetragonal-orthorhombic phase transition pathway to engineer domain orientations and further polarization in polycrystalline Hf0.5Zr0.5O2 using single-crystalline TiN substrates. Specifically, (001)O and/or (010)O domains, which fully contribute to remanent polarization under an electric field, are controllable in Hf0.5Zr0.5O2 on TiN (001) and (111), enhancing remanent polarization compared to that on TiN (110). The key is the hidden transition from the tetragonal phase’s longest c-axis to the orthorhombic phase’s shorter b O /c O -axis, alongside the reported one to the longest a O -axis, assisted by periodic dislocations at the TiN/Hf0.5Zr0.5O2 interface. These findings shed light on governing the polarization of Hf0.5Zr0.5O2 films by controlling the interface dislocations and further domain orientations.